Magnetic classification of meteorites (V) : Iron meteorites - Nagata, Takesi (1982)
P(論文) Sixteen iron meteorites are magnetically classified into three major classes; hexahedrite plus Ni-poor ataxite, octahedrite and Ni-rich ataxite on the basis of their thermomagnetic characteristics. Magnetic parameters for the classification scheme are ratio of saturation magnetization of kamacite, I_s(α), to total saturation magnetization, I_s, namely I_s(α)/I_s, and transition temperature from γ-phase to α-phase of kamacite in the cooling process, Θ^*_<γ→α>. On an I_s(α)/I_s vs. Θ^*_<γ→α> diagram, the three major classes of iron meteorites are represented by their respective domains well separated from one another. departmental bulletin paper